Thos Ashe funeral [1917?] : volley over grave (1917)
Crowd observing Irish soldiers firing a volley over the grave of Thomas Ashe at his funeral in Glasnevin Cemetery, Dublin.
Title inscribed on verso in ink.
catalogued
Keywords: Ashe, Thomas, -- 1885-1917 -- Death and burial; Funeral rites and ceremonies -- Ireland; Soldiers -- Ireland -- 1910-1920; Ireland -- History -- Easter Rising, 1916; Photographic prints -- Irish -- 1910-1920; Portrait prints -- Irish -- 1910-1930